Potassium iodide enhances riboflavin-mediated photodynamic inactivation of Escherichia coli and Penicillium expansum for fresh-cut fruit preservation - Jiayue Jin; Zheng Wu; Yibo Liu; Yile Zhao; Jingying Shi; Da Wang; Xiangzheng Yang; Di Wu; Kunsong Chen (Postharvest Biology and Technology, 2026)

EGCG-functionalized deacetylated konjac glucomannan/carboxylated cellulose nanofiber films: Development, characterization, and application in antibacterial preservation of fresh-cut fruits - Yang Cao; Yile Zhao; Zhixin Li; Di Wu; Chen Chen; Aili Jiang; Xiangzheng Yang; Da Wang; Xian Li; Kunsong Chen (Food Research International, 2026)

An enhanced YOLO-based deep learning framework for automated structural defect inspection in complex backgrounds - Zheyu Liu; Di Su; Youqi Zhang; Da-Wei Lin; Zhen Sun (Engineering Structures, 2026)

Low-loss AgReMo2O8 (Re = Y, Yb) LTCC ceramics designed by Ag+ common-ion effect for dielectric resonator antenna applications - Jian Bao; Jing Guo; Da Tian; Zhen Fang; Zhen-Tao Wang; Yang Liu; Yang Gao; Cai-Hong Zhang; Biao-Bing Jin; Andreu Cabot; Li-Xia Pang; Kar Ban Tan; et al. (Chemical Engineering Journal, 2026)

From exposure to effect: Exploring adverse outcome pathways in fish responses to a large mining disaster - Manuela Santos Santana; Leonardo Sandrini-Neto; Gisele Daiane Pinha; Fabio Cavalca Bom; Fabiana de Matos Costa; Nelson de Almeida Gouveia; Kyssyanne Samihra Santos Oliveira; Nadson Ressyè Simões; Beatrice Padovani Ferreira; Renata Caiado Cagnin; Cesar Alexandro da Silva; Eduardo Schettini Costa; et al. (Environmental Pollution, 2026)

Photothermal Agents in Cancer Therapy: Applications and Development Prospects - Shiyu He; Shuaipeng Feng; Yiming Han; Qingqing Xu; Jiaru Lan; Donghua Di; Da Wang; Siling Wang; Huan Zhai; Qinfu Zhao (Chemical Engineering Journal, 2026)

Molecular detection of pathogenic Leptospira spp. in mares with reproductive disorders enrolled in embryo transfer programs - Gustavo de Oliveira Alves Pinto; Eduarda Faria Raymundo; Gabriela Gonçalves da Silva; André de Souza Santos; Dhebora Silvério Correia; Gabriela Reis Xavier; Erika Fernanda Torres Samico-Fernandes; Gustavo Ferrer Carneiro; Maria Isabel Nogueira Di Azevedo; Rinaldo Aparecido Mota (Journal of Equine Veterinary Science, 2026)

Diagnosis of acetaminophen and codeine poisoning in a dog using earwax analysis by headspace gas chromatography-mass spectrometry (HS/GC-MS) - Monica Chacon de Vicente; Alexandre Có Mangoni Barros; Gabriela Scarpin de Souza; Lais di Pauli Taborda Prado; João Marcos Gonçalves Barbosa; Rayanne Henrique Santana da Silva; Leidiane de Souza Gomes; Danieli Brolo Martins; Nelson Roberto Antoniosi Filho; Ana Flávia Machado Botelho (Veterinary Research Communications, 2026)
Poisoning of companion animals resulting from exposure to analgesics intended for human use is a frequent and clinically relevant problem in veterinary practice, usually associated with administration without professional supervision. This can induce severe systemic toxicity. Diagnostic confirmation can be particularly challenging in cases presenting with nonspecific clinical signs or when conventional biological samples are unavailable. This case report describes the innovative use of earwax as a non-invasive biological matrix for toxicological confirmation in veterinary medicine. A 9-year-old male mixed-breed dog was admitted following a traumatic accident and subsequent administration by its owner of a human medication containing acetaminophen and codeine. Clinical evaluation revealed lethargy, hypersalivation, hyporexia, dehydration, and neurological abnormalities. Laboratory findings demonstrated neutrophilic leukocytosis and marked increases in hepatic enzyme activities, consistent with acute hepatocellular injury. Toxicological investigation using headspace gas chromatography–mass spectrometry detected acetaminophen-related signatures in an earwax sample, supporting suspected exposure to the drug. Intensive treatment was promptly initiated and included fluid therapy, antidotal treatment with N-acetylcysteine, opioid antagonism, analgesia, and supportive care. The patient showed progressive clinical improvement, with complete resolution of clinical signs and full recovery. This case highlights the significant risks of administering human medications to companion animals and underscores the need to improve owner awareness of self-medication practices. Furthermore, it demonstrates the diagnostic potential of earwax as a non-invasive biological matrix for toxicological confirmation, expanding the range of complementary diagnostic tools available for veterinary toxicology and supporting improved clinical decision-making in cases of suspected pharmaceutical intoxication.

Synergistic hurdle technology for postharvest preservation of Chinese bayberries: Combining indirect plasma processed air and peracetic acid to reduce chemical dosage - Xiangzheng Yang; Dandan Zheng; Yongrui Ti; Huan Lian; Jiahao Zhong; Da Wang; Chaoyi Shen; Di Wu; Qisen Xiang; Jiangkuo Li; Xian Li; Kunsong Chen (Food Chemistry, 2026)

Preparation of polybutylene adipate terephthalate-based degradable nanofibrous membranes loaded with metal-organic frameworks for linear and sustained release of thymol via microfluidic blown spinning for fruit preservation - Feifei Wang; Xiaohong Guo; Wenjing Shi; Xiangju Feng; Yongrui Ti; Xiangzheng Yang; Da Wang; Jiangkuo Li; Zhiqiang Wang; Zhengan Yang; Di Wu; Kunsong Chen (Food Packaging and Shelf Life, 2026)

Viral communities as mirrors and vectors: Tracing antibiotic resistome distribution and dissemination across diverse habitats in Macao - Yu-Qiu Ye; Da Lin; Luo-Qin Shen; Di Wu; Ying Li; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2026)

Monitoring the hyporheic zone: a global review and strategic directions for improvement - Daniel da Silva Andrade; Tiziana Di Lorenzo; Silvia Vendruscolo Milesi; Luiz Ubiratan Hepp; Riccardo Mugnai (Environmental Monitoring and Assessment, 2026)
The hyporheic zone (HZ) is a crucial interface in riverbeds that links surface and subterranean waters, supporting a unique ecological community. While recent reviews have explored theoretical and ecological aspects of HZ, this study focuses on evaluating the advances in monitoring the quality and conservation status. We conducted a global systematic review, screening 16,135 articles and retaining a final data pool of 102 peer-reviewed studies published between 1989 and 2024. We address four main areas: (i) spatial and temporal distribution, (ii) monitoring activities, (iii) methodologies employed, and (iv) the impact of legislation. Despite advances in technical knowledge, HZ monitoring efforts remain quantitatively limited. Geographically, research is highly skewed, with Europe (51.0%), Asia (21.6%), and North America (19.6%) dominating the field, while other regions are severely underrepresented. Taxonomically, studies predominantly focus on the entire invertebrate community (35.5%) or microorganisms (30.3%), whereas efficient trait-based approaches remain scarce (6.6%). Methodologically, sampling is largely confined to shallow depths (up to − 50 cm). Furthermore, the enactment of environmental legislation showed a localized, rather than global, stimulus on monitoring outputs. This study emphasizes the urgent need for standardized methodologies, integrated surface–groundwater approaches, and targeted efforts to ensure effective water resource management. Finally, we propose a strategic roadmap with short-, medium-, and long-term actions to guide these improvements.

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Tuning the influent sulfur-to-nitrogen ratio to mitigate nitrous oxide emissions in a sulfite-driven autotrophic denitrification system - Da Di; Mi Xue; Caixia Ping; Xin Zhou (Bioresource Technology, 2026)

Propolis extracts suppress early blight severity in tomato by enhancing antioxidant defenses and phenylpropanoid pathway - Mayara Martins Cardozo; Mateus Brusco de Freitas; Mychelli Preuss da Cruz; Robson Marcelo Di Piero (Journal of Plant Diseases and Protection, 2026)
Early blight, caused by Alternaria spp., is a major tomato disease that reduces yield and fruit quality. The objective of this study was to evaluate the efficacy of hydroalcoholic propolis extracts (PHEs) from five regions of Santa Catarina, Brazil, against A. linariae in tomato plants. The total phenolic content of the extracts ranged from $$\:13.02$$ to $$\:50.62\:μ\:g$$ gallic acid equivalents (GAE) $$\:mL^{-1}.$$ In greenhouse bioassays, PHEs reduced disease severity by over 90%, with SJ1O being the most effective (94.1% reduction, lowest area under the disease progress curve, AUDPC). Systemic activity was observed, with efficacy near in treated leaves and ~ 50% in untreated ones. PHEs also suppressed spore germination (up to 85%) and fungal colonization (up to 87%). Biochemical analyses showed that PHEs enhanced the activities of ascorbate peroxidase (APX), catalase (CAT), superoxide dismutase (SOD), and lipoxygenase (LOX), and stimulated phenylalanine ammonia lyase (PAL) activity and lignin accumulation, leading to lower reactive oxygen species (ROS) accumulation and lipid peroxidation. Collectively, these results demonstrate the novelty of propolis extracts as resistance elicitors in tomato. Importantly, this study provides the first evidence that hydroalcoholic propolis extracts from Santa Catarina, Brasil, can suppress early blight in tomato by activating both antioxidant defenses and phenylpropanoid metabolism, resulting in strong reduction of pathogen development and host tissue damage, and highlighting propolis as a promising, eco-friendly tool for sustainable early blight management.

Inner‐Shelf Geomorphology and Hydrodynamics as Biogeographic Barriers to Long‐Distance Dispersal of the Interstitial Annelid Saccocirrus (Saccocirridae) - Thainá Cortez; Arian Dialectaquiz; Marcelo Dottori; Jon Norenburg; Katrine Worsaae; Alejandro Martínez; Francesca Leasi; Maikon Di Domenico; Sónia Cristina da Silva Andrade (Journal of Biogeography, 2026)
Aim This study aimed to investigate the population structure and demographic history of Saccocirrus pussicus Marcus, 1948, an interstitial annelid that inhabits coarse sandy beaches in Brazil. We tested the hypothesis that the limited space between sediment grains constrains dispersal, resulting in restricted gene flow, despite the presence of a larval stage. We also tested whether oceanic conditions could influence connectivity and the distribution of genetic diversity. Location Samples were collected from coastal sites in Brazil, USA, Cuba, Panama and Italy. Taxon Saccocirrus pussicus Marcus, 1948 (Annelida, Saccocirridae). Methods We analysed fragments of the mitochondrial 16S rRNA and nuclear 28S rRNA genes from 190 Saccocirrus specimens to assess genetic diversity, lineage structure and connectivity patterns. Phylogenetic analyses, gene flow estimates and larval dispersal simulations were performed to infer population structure and migration dynamics. Results Between six and nine evolutionary lineages were identified across all sampled locations. Along the Brazilian coast, seven localities exhibited a high number of shared haplotypes and elevated migration probabilities among distant populations, suggesting extensive admixture over approximately 2000 km. These results refute the initial hypothesis of limited dispersal. Gene flow estimates and larval dispersal simulations indicate that migration of S. pussicus occurs from south to north along the Brazilian coast. Nonetheless, there is evidence of isolation between the northernmost and southernmost localities, likely due to the presence of a biogeographic barrier whose nature remains unclear. Main Conclusions Small‐bodied interstitial organisms with planktonic larvae appear to be influenced by coastal transport processes previously recognized only in biogeographic frameworks for larger organisms. Littoral drift and surface circulation can act both as barriers and as facilitators of dispersal. These insights underscore the need for further comparative studies across taxa to clarify the mechanisms driving population connectivity in interstitial habitats at macrogeographic scales.

IncobotulinumtoxinA for the Treatment of Glabellar and Forehead Dynamic Lines: A Brazilian Multicenter Real-Life Study - Ana Lucia Gonzaga da Cunha; Rossana Vasconcelos; David Di Sessa; Gabriel Sampaio; Pitila Ramalhoto; Bruno F. Zampieri; Bárbara S. Deus; Suyan Vasconcelos; Talitha Bellote; Juliano Carvalho; Giseli Petrone; Vinicius Figueredo; et al. (Toxicon, 2026)

Schoolchildren’s exposure to potentially toxic metals/metalloids and cognitive impairments in communities of the Brazilian Amazon new agricultural frontiers - J.A. Menezes-Filho; E.C.A. Di Giuseppe; T.M.P. Moraes; B.A.T. Couto; B.S. Ferreira; N.B. Matos da Silva; C.S. Lima; W.P. Moraes; A.C. Florentino; F. Barbosa-Jr; C.J.S. Passos (NeuroToxicology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

FCMI analysis of multiphysics coupling of fuel rods at the end of cycle of Xi’an pulsed reactor - Zhaohao Wang; Jinkai Zhang; Tianliang Hu; Di Yun; Duoyu Jiang; Da Li; Lixin Chen; Wenbo Liu (Annals of Nuclear Energy, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Three new flavonoid glycosides from the herbaceous stems of Ephedra intermedia - Ying Niu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Di Lu; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Product Research, 2026)

Mercury contamination in Brazil related to (historical) artisanal and small-scale gold mining activity: a narrative review with quantitative synthesis - Marcelo da Silveira Tortolero Arauj Lourenço; David Debruyne; Rosa Maria Di Maggio; Chiara Germinario; Celestino Grifa; Francesco Izzo; Alessio Langella; Lara Silva de Paula; Fábio Augusto da Silva Salvador; Mariano Mercurio (Environmental Geochemistry and Health, 2026)

Preparation of ZnSO4 cross-linked double-network hydrogels via synergistic ionic and Hofmeister effects as in-situ fruit packaging integrating cushioning and monitoring - Wenjun Wu; Jiahao Zhong; Zhichao Yang; Ziqiang Qin; Chaoyi Shen; Zihan Cai; Xiangzheng Yang; Qilei Li; Da Wang; Jiangkuo Li; Xian Li; Di Wu; et al. (Food Packaging and Shelf Life, 2025)

Combined use of electrochemical, dissolved air flotation, and microfiltration in the treatment of offshore produced water - M. A. P. Cechinel; M. C. Proner; D. G. Della Rocca; S. L. de Carvalho Neto; S. E. Weschenfelder; A. da Silva; A. Ambrosi; M. Di Luccio; R. F. P. M. Moreira (International Journal of Environmental Science and Technology, 2025)

Steam distillation, supercritical fluid extraction, and anti- Trypanosoma cruzi activity of compounds from pink pepper ( Schinus terebinthifolius Raddi) - Rebeca Maria Neto; Emmanuele Di Fabio; Marina de Monroe Gonçalves; Mònica Benicia Mamián López; Célio Fernando Figueiredo Angolini; Priscilla Carvalho Veggi; André Gustavo Tempone; Juliana Martin do Prado; João Henrique Ghilardi Lago; Bruno Guzzo da Silva (Natural Product Research, 2025)

Investigation of convolutional variational autoencoders for facies calibration within ensemble-smoother multiple data assimilation - Emanuela Abbate; Laura Dovera; Davide Di Curzio; Andrea Da Pra (Computational Geosciences, 2025)

Thermal comfort and seminal traits in stallion reproduction: New methods to understand these relationships - Luiza Maria Feitosa Ribeiro; João Victor Bersot Gomes; Wilder Hernando Ortiz Vega; Andressa da Silva Alves; Maurício Netto Machado; Luan Junio Wutke; Célia Raquel Quirino; Roberta Carvalho Basile; Paula Alessandra Di Filippo (Journal of Equine Veterinary Science, 2025)

A novel zooplankton-based environmental monitoring tool for coastal impacted areas: The case of the Doce River dam rupture - Gustavo Martins Rocha; Bianca Salvador; Gabriel Harley Costa Santos; Laura Rodrigues da Conceição; Priscila Teixeira-Amaral; Maikon Di Domenico; Diego de Arruda Xavier; Eduardo Schettini Costa; Renata Caiado Cagnin; Cesar Alexandro da Silva; Mayara Bandeira; Mônica de Souza Mendes; et al. (Estuarine, Coastal and Shelf Science, 2025)

Extracellular polymeric substance-intercalated MXene membrane for osmotic power generation - Da-Qi Cao; Kai Tang; Guri Yihuo; Yan Jin; Yi-Xuan Song; Yun-Feng Wu; Wen-Yu Zhang; Zhongguo Zhang; Ming-Guo Ma; Li Song; Xiao-Di Hao (Chemical Engineering Journal, 2025)

The effect of chlorinated cyanurates on the formation of disinfection byproducts in the production of reuse water from secondary sanitary effluent - Cristina Filomêna Pereira Rosa Paschoalato; Talita Rafaella da Silva Boldrin Dias; Márcia Maísa de Freitas Afonso; Marília Vanconcellos Agnesini; Guilherme Sgobbi Zagui; Angela Di Bernardo Dantas; Murilo Daniel de Mello Innocentini (Journal of Environmental Chemical Engineering, 2025)

Self-powered and self-sensing water meter using contact-separation triboelectric nanogenerator with harvesting local head loss - Da-Qi Cao; Xiao-Dan Liu; Rong-Kun Fang; Guri Yihuo; Yun-Feng Wu; Zhan-Gao Huang; Wen-Yu Zhang; Xiangyu Chen; Xiao-Di Hao (Journal of Water Process Engineering, 2025)

Effects of ruminal infusion of unsaturated fatty acids on digestive parameters, milk fatty acids and ruminal kinetics in Jersey cows supplemented with chitosan - Vinícius Monteiro de Carvalho; Olga Cedro de Menezes; Sarah Nogueira da Silva e Silva; Douglas dos Santos Pina; Gleidson Giordano Pinto de Carvalho; Ricardo Diniz Guerra e Silva; Maria Leonor Garcia Melo Lopes de Araújo; Cláudio Vaz Di Mambro Ribeiro; Polyana Pizzi Rotta; Lara Maria Santos Brant; José Esler de Freitas Júnior (Tropical Animal Health and Production, 2025)

Collision and clustering behavior of high-viscosity fluid-particle flow in bent pipes based on LBM-DEM - Jie-Di Weng; Yong-Zheng Jiang; Lian Tao; Da-Lian Yang (Ocean Engineering, 2025)

Toxesbium gen. nov., the first definitive member of Ernobiinae from mid-Cretaceous amber of northern Myanmar (Coleoptera: Ptinidae) - Yan-Da Li; T. Keith Philips; Di-Ying Huang; Chen-Yang Cai (PalZ, 2025)

Resilience patterns in the analysis of social-ecological networks of small-scale fishing in a subtropical estuarine system - Michele Cristina Nether; José Milton Andriguetto-Filho; Mauricio Almeida Noernberg; André Pereira Cattani; Isabeli Cristina Gomes Mesquista; Rodrigo Pereira Medeiros; Carlos Schneider Batista; José Hugo Dias Godim Guanais; Paulo da Cunha Lana; Maikon Di Domenico (Ocean & Coastal Management, 2024)

Decreases in serum PFAS are associated with decreases in serum lipids: A longitudinal study on a highly exposed population - Erich Batzella; Tony Fletcher; Gisella Pitter; Filippo da Re; Francesca Russo; Andrea di Nisio; Cristina Canova (Science of The Total Environment, 2024)

Optimization of storage yards in sustainable forest management in the amazon - Débora Monteiro Gouveia; Julio Eduardo Arce; Eduardo da Silva Lopes; Fabiane Aparecida Retslaff Guimaraes; Rodrigo dos Santos Lima; Luciana Di Paula Assunção Pereira (Journal of Environmental Management, 2024)

Comparison between new enhanced thermal response test methods for underground heat exchanger sizing - A. Galgaro; R. Da Re; A. Carrera; E. Di Sipio; G. Dalla Santa (Geomechanics for Energy and the Environment, 2024)

Microfluidic-blow-spinning of carvacrol-loaded porphyrin metal − organic framework nanofiber films with synergistic antibacterial capabilities for food packaging - Zi-An Deng; Menglu Wu; Chaoyi Shen; Xiangzheng Yang; Da Wang; Jiangkuo Li; Di Wu; Kunsong Chen (Food Chemistry, 2024)

Deacetylated konjac glucomannan films functionalised with carboxylated cellulose nanofiber and anti-browning components for fresh-cut apple preservation - Yile Zhao; Zheng Wu; Chen Chen; Olaniyi Amos Fawole; Aili Jiang; Xiangzheng Yang; Da Wang; Xian Li; Di Wu; Kunsong Chen (Food Packaging and Shelf Life, 2024)

Herbal-based therapeutics for diabetic patients with SARS-Cov-2 infection - Yousef Rasmi; Ighli di Bari; Shah Faisal; Munima Haque; Pornanong Aramwit; Aline da Silva; Elmira Roshani Asl (Molecular Biology Reports, 2024)

miR-144-3p Targets GABRB2 to Suppress Thyroid Cancer Progression In Vitro - Cheng Xiu; Xiaocong Deng; Da Deng; Tao Zhou; Chuiguang Jiang; Di Wu; Yong Qian (Cell Biochemistry and Biophysics, 2024)

Three-dimensional CSAMT Forward Modeling of Potential Landslide Sliding Surfaces Using Finite Element Method - Ruo Wang; Qingyun Di; Da Lei; Changmin Fu; Pengfei Liang; Miaoyue Wang (Applied Geophysics, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Two undescribed monoterpenoids from the fruit of Gardenia jasminoides Ellis - Di Lu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Ying Niu; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Local hydrography and interactions with benthic megafauna explain fish assemblage structure on the shallow inner shelf of Paraná, southern Brazil - Matheus H. Luchese; Maikon Di Domenico; Roberto Schwarz; Cláudio D. da Natividade; Carlos A. Borzone; Henry L. Spach; José M. Andriguetto-Filho (Estuarine, Coastal and Shelf Science, 2024)

Effect of a Monoglyceride Blend in Nile Tilapia Growth Performance, Immunity, Gut Microbiota, and Resistance to Challenge against Streptoccocosis and Francisellosis - Natália Amoroso Ferrari; Raffaella Menegheti Mainardi; Mayza Brandão da Silva; Gabriel Diogo Guimarães; João Vitor Godoy Takashe; Admilton Gonçalves de Oliveira Junior; Ricardo Mitsuo Hayashi; Giovana Wingeter Di Santis; Ulisses de Pádua Pereira (Fishes, 2024)
This study evaluated the effects of supplementing the diet of juvenile Nile tilapia (Oreochromis niloticus), which weighs approximately 20 g, with a blend of monoglycerides (glycerides linked to a fatty acid molecule) for 20 days during a pre-experimental challenge via the intraperitoneal route (IP). Growth performance, immunological parameters, intestinal microbiota, tissue damage, and resistance against the pathogens Streptococcus agalactiae serotypes Ib and III and Francisella orientalis were evaluated. The experimental design included a negative control (NC), a product control (NPC), a positive control for each pathogen (PC), and three groups treated with different doses (0.15, 0.25, and 0.5%). After the challenge, mortality was significantly lower in the groups treated and challenged with S. agalactiae. The treated groups showed better weight gain and food conversion rates. Innate immunity parameters showed no differences between treatments, and there was no good stimulation of diversity in the intestinal microbiota. However, in treated groups, there was a reduction in opportunistic bacteria that could cause secondary infections and increased the presence of beneficial bacteria in the intestinal tract. In this way, it is possible to validate the beneficial effects of monoglycerides as a nutritional additive for tilapia farms against streptoccocosis.

Quality of honey from Tubuna bees (Scaptotrigona bipunctata) fresh, thermally treated and during storage - Aline Danielle Di Paula Silva Rodrigues; Gabrielle da Graça Hagy de Oliveira; Ana Flávia Mendonça Santos; Schaina Andriela Pontarollo Etgeton; Anne Caroline Rodrigues Silva; Renata Túlio Küster Bernardo dos Anjos; Lais de Oliveira Seiscentos; Lize Stangarlin Fiori; Suelen Ávila; Sila Mary Rodrigues Ferreira (Journal of Stored Products Research, 2024)

Double gradient coupling heterostructure design accurately regulates the anion process of the Li-rich cathode - Chaoliang Zheng; Da Zhang; Di Zhang; Jianling Li (Chemical Engineering Journal, 2024)

Regulation of gene expression in the secondary metabolic synthesis pathway of Lonicera japonica Flos by yeast polysaccharides - Xu-peng Gu; Lin-lin Yang; Da-ming Qi; Di Zhang; Tian-liang Liu; Cheng-ming Dong (Physiology and Molecular Biology of Plants, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Contact-electro-catalysis for degradation of trace antibiotics in wastewater - Da-Qi Cao; Rong-Kun Fang; Yi-Xuan Song; Ming-Guo Ma; Haiyan Li; Xiao-Di Hao; Rongling Wu; Xiangyu Chen (Chemical Engineering Journal, 2024)

Using bioinformatic resources for a systems-level understanding of phosphorylation - Di Peng; Da Jia; Hongguang Xia; Luoying Zhang; Pengyu Huang; Yu Xue (Science Bulletin, 2024)

Corynebacterium pseudotuberculosis biovar ovis strains isolated from small ruminants herds from the Brazilian Amazon present clonal genomic profile - Suania Maria do Nascimento Sousa; Alyne Cristina Sodré Lima; Vitória Almeida Gonçalves de Moura; Jackeline Rossetti Mateus; Lucimar Di Paula dos Santos Madeira; Ricardo Wagner Portela; Rinaldo Batista Viana; Rommel Thiago Jucá Ramos; Lucy Seldin; Herve Louis Ghislain Rogez; Artur Luiz da Costa da Silva; Joana Montezano Marques (Small Ruminant Research, 2024)

New volcanological, 40Ar/39Ar dating and paleomagnetic record from Trindade Island and stratigraphic implications - N.G. Pasqualon; J.F. Savian; E.F. Lima; W.P. de Oliveira; G.A. Hartmann; C.M.S. Scherer; L.M.M. Rossetti; F.R. da Luz; R.I.F. Trindade; E.B. Cahoon; D.P. Miggins; A. Koppers; et al. (Quaternary Geochronology, 2024)

Aqueous enzymatic extraction of macauba (Acrocomia aculeata) pulp oil: A green and sustainable approach for high-quality oil production - Guilherme Dallarmi Sorita; Simone Palma Favaro; Dasciana de Sousa Rodrigues; Wellington Paula da Silva Junior; Wesley Gabriel de Oliveira Leal; Alan Ambrosi; Marco Di Luccio (Food Research International, 2024)

Ferric uptake regulator (fur) affects the pathogenicity of Aeromonas veronii TH0426 by regulating flagellar assembly and biofilm formation - Jin-shuo Gong; Ying-da Wang; Yan-long Jiang; Di Zhang; Ya-nan Cai; Xiao-feng Shan; He Gong; Hao Dong (Aquaculture, 2024)

Synergistic effects of PVDF membrane surface functionalization with polydopamine and titanium dioxide for enhanced oil/water separation and photocatalytic behavior - Anderson Felipe Viana da Silva; Daniela Gier Della Rocca; Regina Fátima Peralta Muniz Moreira; J. Vladimir Oliveira; Alan Ambrosi; Marco Di Luccio (Journal of Environmental Chemical Engineering, 2024)

Carboxymethyl chitosan and polycaprolactone-based rapid in-situ packaging for fruit preservation by solution blow spinning - Chaoyi Shen; Xiangzheng Yang; Da Wang; Jiangkuo Li; Changqing Zhu; Di Wu; Kunsong Chen (Carbohydrate Polymers, 2024)

Update on Brazilian essential oils with leishmanicidal activity - Ingrid Borges Siqueira; Yvanna Louise Di Christine Oliveira; Sona Jain; Audrey Rouse Soares Tavares Silva; Luiz Fernando de Jesus Nascimento; Márcio Luiz da Gama Lisboa; Tiago Branquinho Oliveira; Damião Pergentino de Sousa; Ana Andrea Teixeira Barbosa; Silvio Santana Dolabella (Phytochemistry Reviews, 2024)

The impact of urbanization on heat stress in Brazil: A multi-city study - Eduardo Krüger; João Paulo Assis Gobo; Graziela Tosini Tejas; Reginaldo Martins da Silva de Souza; João Batista Ferreira Neto; Gabriel Pereira; David Mendes; Claudia Di Napoli (Urban Climate, 2024)

Multidisciplinary study of the Lower Palaeolithic site of Cimitero di Atella (Basilicata), Italy - Roxane Rocca; Paolo Giannandrea; Alison Pereira; Jean-Jacques Bahain; Francesco Boschin; Amélie Da Costa; Federico Di Rita; François Fouriaux; Alessio Iannucci; Lucie Germond; Dario Gioia; Donatella Magri; et al. (Quaternary International, 2023)

The ice resistance of self-centering jacket offshore platform with concrete filled double-skin legs: Experimental study and numerical analysis - Feifei Liu; Jigang Zhang; Jia Sun; Di Zhao; Da Gao; Zhehao Ma; Hanyu Song; Ruixue Wu; Weicheng Zhang (Ocean Engineering, 2023)

The PlastOPol system for marine litter monitoring by citizen scientists - Di Wu; Jincheng Liu; Manuel Cordova; Christina Carrozzo Hellevik; Jakob Bonnevie Cyvin; Allan Pinto; Ibrahim A. Hameed; Helio Pedrini; Ricardo da Silva Torres; Annik Magerholm Fet (Environmental Modelling & Software, 2023)

Valorization of royal palm tree agroindustrial waste via pyrolysis with a focus on physicochemical properties, kinetic triplet, thermodynamic parameters, and volatile products - José Luiz Francisco Alves; Jean Constantino Gomes da Silva; Guilherme Davi Mumbach; Santiago Arias; José Geraldo A. Pacheco; Michele Di Domenico; Cintia Marangoni (Biomass and Bioenergy, 2023)

Real life data on nintedanib safety: idiopathic pulmonary fibrosis versus systemic sclerosis-interstitial lung disease and strategies adopted to manage adverse effects - Marco Di Battista; Laura Tavanti; Francesco Pistelli; Laura Carrozzi; Mattia Da Rio; Alessandra Rossi; Lorenzo Puccetti; Antonio Tavoni; Chiara Romei; Riccardo Morganti; Alessandra Della Rossa; Marta Mosca (Inflammopharmacology, 2023)
Objective Nintedanib (NIN) is an antifibrotic drug approved to slow the progression of idiopathic pulmonary fibrosis (IPF) and systemic sclerosis-related interstitial lung disease (SSc-ILD). NIN can frequently cause gastrointestinal adverse effects. We aimed to investigate the NIN safety profile in a real life setting, comparing IPF and SSc-ILD patients and evaluating the strategies adopted to manage NIN adverse effects. Methods Patients taking NIN for IPF or SSc-ILD were enrolled. Alongside epidemiological and disease-specific data, the period of NIN use and the need for dosage reduction and/or interruption were investigated. Particular attention was paid to possible adverse effects and strategies adopted to manage them. Results Twenty-seven SSc-ILD and 82 IPF patients were enrolled. No significant differences emerged between the two cohorts regarding the frequency of any possible adverse effect. Although the rates of NIN dosage reduction or interruption were similar between the two subgroups, SSc-ILD presented a mean period before NIN dosage reduction and NIN interruption significantly shorter than IPF (3 ± 2.6 vs 10.5 ± 8.9 months—p < 0.001 and 2.3 ± 0.5 vs 10.3 ± 9.9 months—p = 0.008, respectively). Several different strategies were tried to manage NIN adverse effects: especially in SSc-ILD, the variable combination of diet adjustment set by a nutritionist, probiotics and diosmectite was ultimately successful in maintaining patients on an adequate dose of NIN. Conclusion We presented data on the NIN safety profile in a real life setting, which was similar between SSc-ILD and IPF. A combination of multiple managing strategies and dose adjustment appears essential to cope optimally with NIN adverse effects.

Multiple Palaeozoic–Mesozoic orogenic events in the SE Yangtze Block, China: evidence from the petrogenesis and deformation of gneissic granites from the Nanwenhe metamorphic dome and regional correlation analysis - Xinming Zhang; Da Zhang; Jinbo Pan; Minfeng Bi; Ganguo Wu; Xiaolong He; Bojie Hu; Chaoyang Que; Yongjun Di; Wei Xue (International Geology Review, 2023)

The science we need for the beaches we want: frontiers of the flourishing Brazilian ecological sandy beach research - Guilherme Nascimento Corte; Yasmina Shah Esmaeili; Tatiana Fabricio Maria; Leonardo Lopes Costa; Gustavo Mattos; Helio Herminio Checon; Nicole Malinconico; Paulo Cesar Paiva; Paula Debiasi; Tatiana Cabrini; Victor Corrêa Seixas; Eduardo Bulhões; et al. (Frontiers in Marine Science, 2023)

Recent advances in surface modification using polydopamine for the development of photocatalytic membranes for oily wastewater treatment - Anderson Felipe Viana da Silva; Jonas da Silva; Renata Vicente; Alan Ambrosi; Guilherme Zin; Marco Di Luccio; José Vladimir de Oliveira (Journal of Water Process Engineering, 2023)

Effects of a Single Intra-Articular Injection of 2% Lidocaine or 0.5% Bupivacaine on Synovial Fluid Acute Phase Protein Concentrations in Healthy Horses - Gabriel Carvalho dos Santos; Paula Alessandra Di Filippo; Leandro A. da Fonseca; Célia Raquel Quirino (Journal of Equine Veterinary Science, 2023)

Dead-end forward osmosis as an alternative for deep sludge dewatering: Evaluation method and characteristics analysis - Da-Qi Cao; Hui Liu; Feng Tian; Wen-Yu Zhang; Xiao-Di Hao; Eiji Iritani; Nobuyuki Katagiri (Chemical Engineering Journal, 2023)

Thiosulfate pretreatment enhancing short-chain fatty acids production from anaerobic fermentation of waste activated sludge: Performance, metabolic activity and microbial community - Boyi Cheng; Yayi Wang; Da Zhang; Di Wu; Feixiang Zan; Jie Ma; Lei Miao; Zongping Wang; Guanghao Chen; Gang Guo (Water Research, 2023)

Effect of an organic acid blend in Nile tilapia growth performance, immunity, gut microbiota, and resistance to challenge against francisellosis - Vanessa Gomes da Silva; Leonardo Mantovani Favero; Raffaella Menegheti Mainardi; Natália Amoroso Ferrari; Roberta Torres Chideroli; Giovana Wingeter Di Santis; Felipe Pinheiro de Souza; Arthur Roberto da Costa; Daniela Dib Gonçalves; Waldo G. Nuez-Ortin; Maria Mercè Isern-Subich; Admilton Gonçalves de Oliveira-Junior; et al. (Research in Veterinary Science, 2023)

Polybaric fractional crystallization-driven magma differentiation in continental arcs: Insights from the intrusive complex in Langshan arc, southeastern Central Asian Orogenic Belt - Min Liu; Shaocong Lai; Da Zhang; Renzhi Zhu; Jiangfeng Qin; Yu Zhu; Fangyi Zhang; Yongjun Di (Lithos, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

BMSCs-derived Mitochondria Improve Osteoarthritis by Ameliorating Mitochondrial Dysfunction and Promoting Mitochondrial Biogenesis in Chondrocytes - Mingchuan Yu; Di Wang; Xiang Chen; Da Zhong; Jun Luo (Stem Cell Reviews and Reports, 2022)

Trophic ecology of Amazonian River dolphins from three rivers in Brazil and Bolivia - Aldo Echeverria; Silvina Botta; Miriam Marmontel; Gabriel Melo-Santos; Pedro Fruet; Marcelo Oliveira-da-Costa; Marc Pouilly; Juliana Di Tullio; Paul Andre Van Damme (Mammalian Biology, 2022)

Apparent digestibility and ingestive behavior of Nellore bulls with low and high residual feed intake - Rayanne Galdino Menezes; Juliano José de Resende Fernandes; Alana Maria Menezes Di Calaça; Emmanuel Arnhold; Marcia Helena Machado da Rocha Fernandes; Victor Rezende Moreira Couto (Tropical Animal Health and Production, 2022)

Genome-wide identification and expression analysis of JmjC domain–containing genes in grape under MTA treatment - Yi-Zhe Cheng; Guang-Qi He; Sheng-Di Yang; Shuai-Hui Ma; Jin-Ping Ma; Fang-Hui-Zi Shang; Xu-Fei Li; Hui-Ying Jin; Da-Long Guo (Functional & Integrative Genomics, 2022)

A single-cell survey unveils cellular heterogeneity and sensitive responses in mouse cortices induced by oral exposure to triphenyl phosphate - Di Ji; Yuejin Yu; Qicheng Zhu; Xianjie Li; Xiali Zhong; Zhuyi Zhang; Weijian Ke; Congying Niu; Can Wang; Jingwei Wu; Da Chen; Maoyong Song; et al. (Archives of Toxicology, 2022)

Study on the formation of gangue wall and the stress distribution of surrounding rock in gob side entry with roof cutting - Guo Peng-fei; Lian Hong-da; Ye Keng-keng; Tao Zhi-gang; Yuan Ya-di; Zhen En-ze (Arabian Journal of Geosciences, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Resistance of strawberries to Xanthomonas fragariae induced by aloe polysaccharides and essential oils nanoemulsions is associated with phenolic metabolism and stomata closure - Caroline Luiz; Nilmara Pereira Caires; Tarsis de Aguiar; Juliane Mendes Lemos Blainski; Julia da Silva Behs; Danila Souza Oliveira Coqueiro; Robson Marcelo Di Piero (Australasian Plant Pathology, 2022)

Insight into the α-glucosidase-inhibiting mechanism of β-PGG, a commonly occurring polyphenol in diets - Cheng-Di Huang; Hang-Hang Zheng; Xiao-Yue Zhang; Da-Zhi Liu; Jin-Ming Gao; Qiang Zhang (Natural Product Research, 2022)

Physicochemical composition, fatty acid profile and sensory attributes of meat (longissimus lumborum muscle) from Nellore and Nellore-cross bulls - Vanessa Pereira Macedo; Rebeca Dantas Xavier Ribeiro; Sergiane Alves de Araújo; Mateus Neto Silva Souza; Ederson Américo de Andrade; Cláudio Vaz Di Mambro Ribeiro; Carolina Oliveira de Souza; Thadeu Mariniello Silva; Analívia Martins Barbosa; Leilson Rocha Bezerra; Jarbas Miguel da Silva Júnior; Ronaldo Lopes Oliveira (Tropical Animal Health and Production, 2022)

Biocompatible self-healing hydrogels based on boronic acid-functionalized polymer and laponite nanocomposite for water pollutant removal - Xue-Ting Wang; Xudong Deng; Tuo-Di Zhang; Xi Zhang; Wen-Pu Shi; Jialiang Lai; Hongwei Zhou; Ya-Jing Ye; Chen-Yan Zhang; Da-Chuan Yin (Environmental Chemistry Letters, 2022)

Identification and expression analysis of grape LRK10L-2 genes during grape fruit development - Jin-Ping Ma; Xue-Ren Yin; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Sheng-Di Yang; Hui-Ying Jin; Guang-Qi He; Da-Long Guo (Plant Biotechnology Reports, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Development of 3D cultures of zebrafish liver and embryo cell lines: a comparison of different spheroid formation methods - Irisdoris Rodrigues de Souza; Andrezza Di Pietro Micali Canavez; Desiree Cigaran Schuck; Viviana Stephanie Costa Gagosian; Isisdoris Rodrigues de Souza; Taynah Vicari; Edvaldo da Silva Trindade; Marta Margarete Cestari; Marcio Lorencini; Daniela Morais Leme (Ecotoxicology, 2021)

Summary of technology for a comprehensive geophysical exploration of gold mine in North China Craton - Qingyun Di; Guoqiang Xue; Da Lei; Qingdong Zeng; Changmin Fu; Zhiguo An (Science China Earth Sciences, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

[10]-Gingerol-Loaded Nanoemulsion and its Biological Effects on Triple-Negative Breast Cancer Cells - Ideli Zanesco-Fontes; Ana Carolina Lopes Silva; Patrícia Bento da Silva; Jonatas Lobato Duarte; Leonardo Delello Di Filippo; Marlus Chorilli; Marcia Regina Cominetti; Ana Carolina Baptista Moreno Martin (AAPS PharmSciTech, 2021)

Urban adaptation index: assessing cities readiness to deal with climate change - Eduardo Alves Neder; Fabiano de Araújo Moreira; Michele Dalla Fontana; Roger Rodrigues Torres; David Montenegro Lapola; Maria da Penha Costa Vasconcellos; Ana Maria Barbieri Bedran-Martins; Arlindo Philippi Junior; Maria Carmen Lemos; Gabriela Marques Di Giulio (Climatic Change, 2021)

Exploring Açaí Seed (Euterpe oleracea) Pyrolysis Using Multi-component Kinetics and Thermodynamics Assessment Towards Its Bioenergy Potential - José Luiz Francisco Alves; Jean Constantino Gomes Da Silva; Michele Di Domenico; Wendell Venicio De Araujo Galdino; Silvia Layara Floriani Andersen; Ricardo Francisco Alves; Rennio Felix De Sena (BioEnergy Research, 2021)

Experimental Rehabilitation of Three Concrete, Urban Stretches Streams Through Biophilic Interventions Designed: Environmental Evaluations - Alexandre Marco da Silva; Rosiane Argenton e Silva; Kristiane Ramos Primo; Beatriz Capelo Olímpio; Gabriela Bassi Silva; Caroline Terzella Di Giorgio (Water, Air, & Soil Pollution, 2021)

Demonstrating the Suitability of Tamarind Residues to Bioenergy Exploitation Via Combustion Through Physicochemical Properties, Performance Indexes, and Emission Characteristics - José Luiz Francisco Alves; Jean Constantino Gomes da Silva; Guilherme Davi Mumbach; Michele Di Domenico; Rennio Felix de Sena; Ricardo Antonio Francisco Machado; Cintia Marangoni (BioEnergy Research, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Tomato near isogenic lines to unravel the genetic diversity of S. pimpinellifolium LA0722 for fruit quality and shelf life breeding - Melisa Di Giacomo; Marianela Dana Luciani; Vladimir Cambiaso; Roxana Zorzoli; Gustavo Rubén Rodríguez; Javier Hernán Pereira da Costa (Euphytica, 2020)

Physiological and histological aspects of innate and shiitake-induced resistance against bacterial spot on tomatoes - Tarsis de Aguiar; Eder Carlos Schimidt; Argus Cezar da Rocha Neto; Robson Marcelo Di Piero (European Journal of Plant Pathology, 2020)

Patterns of antimicrobial consumption in neonatal and pediatric intensive care units in Germany and Brazil - André Ricardo Araujo da Silva; Elena Jaszkowski; Tilmann Schober; Ulrich von Both; Melanie Meyer-Buehn; Amanda Fáris Marques; Beatriz Farkas; Bernardo Silva de Abreu; Clara Biscaia di Biase; Jully Miyoshi Takahashi; Luisa Dutra de Castro; Izabel Alves Leal; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Correction to: Bridging the gap between will and action on climate change adaptation in large cities in Brazil - Gabriela Marques Di Giulio; Roger Rodrigues Torres; David M. Lapola; Ana Maria Bedran-Martins; Maria da Penha Vasconcellos; Diego Rafael Braga; Marcos Paulo Fuck; Yohanna Juk; Veruska Nogueira; Ana Carolina Penna; Tiago Jacaúna; Marcelo Fetz; et al. (Regional Environmental Change, 2019)

Bridging the gap between will and action on climate change adaptation in large cities in Brazil - Gabriela Marques Di Giulio; Roger Rodrigues Torres; David M. Lapola; Ana Maria Bedran-Martins; Maria da Penha Vasconcellos; Diego Rafael Braga; Marcos Paulo Fuck; Yohanna Juk; Veruska Nogueira; Ana Carolina Penna; Tiago Jacaúna; Marcelo Fetz; et al. (Regional Environmental Change, 2019)

Reflection-Waveform Inversion Regularized with Structure-Oriented Smoothing Shaping - Gang Yao; Nuno V. da Silva; Di Wu (Pure and Applied Geophysics, 2019)

Seismic performance of bridges during the 2016 Central Italy earthquakes - L. Di Sarno; F. da Porto; G. Guerrini; P. M. Calvi; G. Camata; A. Prota (Bulletin of Earthquake Engineering, 2019)

Early-Middle Triassic Intrusions in Western Inner Mongolia, China: Implications for the Final Orogenic Evolution in Southwestern Xing-Meng Orogenic Belt - Min Liu; Shaocong Lai; Da Zhang; Renzhi Zhu; Jiangfeng Qin; Yongjun Di (Journal of Earth Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The apple U-box E3 ubiquitin ligase MdPUB29 contributes to activate plant immune response to the fungal pathogen Botryosphaeria dothidea - Peng-Liang Han; Yuan-Hua Dong; Kai-Di Gu; Jian-Qiang Yu; Da-Gang Hu; Yu-Jin Hao (Planta, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Layer-specific reduced neuronal density in the orbitofrontal cortex of older adults with obsessive–compulsive disorder - Katia Cristina de Oliveira; Lea Tenenholz Grinberg; Marcelo Queiroz Hoexter; Helena Brentani; Claudia Kimie Suemoto; Fabiano Gonçalves Nery; Luzia Carreira Lima; Ana Tereza Di Lorenzo Alho; José Marcelo Farfel; Renata Eloah de Lucena Ferretti-Rebustini; Renata Elaine Paraizo Leite; Ariane Cristine Moretto; et al. (Brain Structure and Function, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

New natural barrigenol-like triterpenoid isolated from the husks of Xanthoceras sorbifolia Bunge - Da Wang; Bin Yu; Chuming Chen; Jie Duan; Donghua Di; Xin Xiong; Yiren Yang; Huiyuan Gao (Natural Product Research, 2018)

Study of Interaction Between Glyphosate and Goethite Using Several Methodologies: an Environmental Perspective - Thiago Orcelli; Eduardo di Mauro; Alexandre Urbano; Daniel F. Valezi; Antonio C. S. da Costa; Cássia Thaïs B. V. Zaia; Dimas A. M. Zaia (Water, Air, & Soil Pollution, 2018)

Accurate seabed modeling using finite difference methods - Gang Yao; Nuno Vieira da Silva; Henry Alexander Debens; Di Wu (Computational Geosciences, 2018)

High thickness histological sections as alternative to study the three-dimensional microscopic human sub-cortical neuroanatomy - Eduardo Joaquim Lopes Alho; Ana Tereza Di Lorenzo Alho; Lea Grinberg; Edson Amaro; Gláucia Aparecida Bento dos Santos; Rafael Emídio da Silva; Ricardo Caires Neves; Maryana Alegro; Daniel Boari Coelho; Manoel Jacobsen Teixeira; Erich Talamoni Fonoff; Helmut Heinsen (Brain Structure and Function, 2018)

The HLA ‐B landscape of Africa: Signatures of pathogen‐driven selection and molecular identification of candidate alleles to malaria protection - Alicia Sanchez‐Mazas; Viktor Černý; Da Di; Stéphane Buhler; Eliška Podgorná; Elodie Chevallier; Lydie Brunet; Stephan Weber; Barbara Kervaire; Manuela Testi; Marco Andreani; Jean‐Marie Tiercy; et al. (Molecular Ecology, 2017)
Human leukocyte antigen ( HLA ) genes play a key role in the immune response to infectious diseases, some of which are highly prevalent in specific environments, like malaria in sub‐Saharan Africa. Former case–control studies showed that one particular HLA ‐B allele, B*53, was associated with malaria protection in Gambia, but this hypothesis was not tested so far within a population genetics framework. In this study, our objective was to assess whether pathogen‐driven selection associated with malaria contributed to shape the HLA ‐B genetic landscape of Africa. To that aim, we first typed the HLA ‐A and ‐B loci in 484 individuals from 11 populations living in different environments across the Sahel, and we analysed these data together with those available for 29 other populations using several approaches including linear modelling on various genetic, geographic and environmental parameters. In addition to relevant signatures of populations’ demography and migrations history in the genetic differentiation patterns of both HLA ‐A and ‐B loci, we found that the frequencies of three HLA alleles, B*53, B*78 and A*74, were significantly associated with Plasmodium falciparum malaria prevalence, suggesting their increase through pathogen‐driven selection in malaria‐endemic environments. The two HLA ‐B alleles were further identified, by high‐throughput sequencing, as B*53:01:01 (in putative linkage disequilibrium with one HLA ‐C allele, C*04:01:01:01) and B*78:01 in all but one individuals tested, making them appropriate candidates to malaria protection. These results highlight the role of environmental factors in the evolution of the HLA polymorphism and open key perspectives for functional studies focusing on HLA peptide‐binding properties.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

Paracoccidioides brasiliensis-associated dermatitis and lymphadenitis in a dog - Selwyn Arlington Headley; Lucienne Garcia Pretto-Giordano; Giovana Wingeter Di Santis; Lucas Alécio Gomes; Rafaela Macagnan; Daniela Farias da Nóbrega; Katherine Moura Leite; Brígida Kussumoto de Alcântara; Eiko Nakagawa Itano; Amauri Alcindo Alfieri; Mario Augusto Ono (Mycopathologia, 2017)

Capuchin monkey biogeography: understanding Sapajus Pleistocene range expansion and the current sympatry between Cebus and Sapajus - Marcela G. M. Lima; Janet C. Buckner; José de Sousa e Silva‐Júnior; Alexandre Aleixo; Amely B. Martins; Jean P. Boubli; Andrés Link; Izeni P. Farias; Maria Nazareth da Silva; Fabio Röhe; Helder Queiroz; Kenneth L. Chiou; et al. (Journal of Biogeography, 2017)
Aim Our aim was to examine gracile capuchin ( Cebus ) and robust capuchin monkey ( Sapajus ) diversification, with a focus on recent Sapajus expansion within Amazonia. We wanted to reconstruct the biogeographical history of the clade using statistical methods that model lineages’ occupation of different regions over time in order to evaluate recently proposed ‘Out of Amazonia’ and ‘Reinvasion of Amazonia’ hypotheses as alternative explanations for the extensive geographical overlap between reciprocally monophyletic gracile ( Cebus ) and robust ( Sapajus ) capuchin monkeys. Location Central and South America. Methods We reconstructed a time‐calibrated molecular phylogeny for capuchins under Bayesian inference from three mitochondrial genes. We then categorized 12 capuchin clades across four Neotropical centres of endemism and reconstructed the biogeographical history of the capuchin radiation using six models implemented in ‘BioGeo BEARS ’. We performed a phylogeographical analysis for a robust capuchin clade that spans the Atlantic Forest, Cerrado, Caatinga and Amazonia. Results We find support for a late Miocene vicariant Cebus‐Sapajus divergence and a Pleistocene Sapajus invasion of Amazonia from the Atlantic Forest. Our new analyses confirm Sapajus diversified first in the Atlantic Forest, with subsequent range expansion into widespread sympatry with Cebus in Amazonia, as well as multiple expansions into drier savanna‐like habitats. We do not find mitochondrial molecular congruence with morphological species distinctions for Sapajus flavius , S. cay , S. macrocephalus , S. libidinosus and S. apella ; instead, these five morphological types together form a single widespread clade (Bayesian posterior probability = 1) with geographical substructure and shared ancestry during the Pleistocene. Main conclusions Our results support vicariance dividing ancestral capuchin populations in Amazonia versus the Atlantic Forest, and a Pleistocene ‘Amazonian invasion’ by Sapajus to explain the present‐day sympatry of Cebus and Sapajus .

The Sweet Passion Fruit (Passiflora alata) Crop: Genetic and Phenotypic Parameter Estimates and QTL Mapping for Fruit Traits - Guilherme da Silva Pereira; Larissa Di Cassia Laperuta; Endson Santana Nunes; Lourdes Chavarría; Maria Marta Pastina; Rodrigo Gazaffi; Isaías Olívio Geraldi; Antonio Augusto Franco Garcia; Maria Lucia Carneiro Vieira (Tropical Plant Biology, 2017)

Designing optimal number of receiving traces based on simulation model - Hu Zhao; Si-Hai Wu; Jing Yang; Da Ren; Wei-Xiu Xu; Di-Ou Liu; Peng-Yu Zhu (Applied Geophysics, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Three-dimensional and stereological characterization of the human substantia nigra during aging - Ana Tereza Di Lorenzo Alho; Claudia Kimie Suemoto; Lívia Polichiso; Edilaine Tampellini; Kátia Cristina de Oliveira; Mariana Molina; Glaucia Aparecida Bento Santos; Camila Nascimento; Renata Elaine Paraizo Leite; Renata Eloah de Lucena Ferreti-Rebustini; Alexandre Valotta da Silva; Ricardo Nitrini; et al. (Brain Structure and Function, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Incorporation of 5-ethynyl-2′-deoxyuridine (EdU) as a novel strategy for identification of the skewed X inactivation pattern in balanced and unbalanced X-rearrangements - Luiza Sisdelli; Angela Cristina Vidi; Mariana Moysés-Oliveira; Adriana Di Battista; Adriana Bortolai; Danilo Moretti-Ferreira; Magnus R. Dias da Silva; Maria Isabel Melaragno; Gianna Carvalheira (Human Genetics, 2016)

Cryptococcus gattii-Induced Infections in Dogs from Southern Brazil - Selwyn Arlington Headley; Giovana Wingeter Di Santis; Brígida Kussumoto de Alcântara; Thais Correa Costa; Elisangela Olegário da Silva; Lucienne Garcia Pretto-Giordano; Lucas Alécio Gomes; Amauri Alcindo Alfieri; Ana Paula Frederico R. L. Bracarense (Mycopathologia, 2015)

Nondestructive Spectroscopic and Imaging Techniques for Quality Evaluation and Assessment of Fish and Fish Products - Hong-Ju He; Di Wu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2015)

Mechanism of action of the tri-hybrid antimicrobial peptide LHP7 from lactoferricin, HP and plectasin on Staphylococcus aureus - Di Xi; Xiumin Wang; Da Teng; Ruoyu Mao; Yong Zhang; Xiaojie Wang; Jianhua Wang (BioMetals, 2014)

Saccocirridae (Annelida) from the southern and southeastern Brazilian coasts - Maikon Di Domenico; Alejandro Martínez; A. Cecilia Z. Amaral; Paulo da Cunha Lana; Katrine Worsaae (Marine Biodiversity, 2014)

A taxonomic overview of marine and estuarine oligochaetes from Brazil - Alessandro L. Prantoni; Maikon Di Domênico; Paulo da Cunha Lana (Marine Biodiversity, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

Chemical composition of the essential oil of Lippia gracilis Schauer leaves and its potential as modulator of bacterial resistance - Vanessa de Carvalho Nilo Bitu; Heberty Di Tarso Fernandes Fecundo; José Galberto Martins da Costa; Henrique Douglas Melo Coutinho; Fabíola Fernandes G. Rodrigues; Nathalia Matos de Santana; Marco Antônio Botelho; Irwin R. Alencar Menezes (Natural Product Research, 2014)

HLA variation reveals genetic continuity rather than population group structure in East Asia - Da Di; Alicia Sanchez-Mazas (Immunogenetics, 2014)

SHRIMP U-Pb zircon geochronology and Nd-Sr isotopic study of the Mamianshan Group: implications for the Neoproterozoic tectonic development of southeast China - Da Zhang; Ganguo Wu; Yongjun Di; Xinqi Yu; Yuruo Shi; Xiangxin Zhang; Qunfeng Wang; Huojian Huang (International Geology Review, 2013)

Sugarcane (Saccharum X officinarum): A Reference Study for the Regulation of Genetically Modified Cultivars in Brazil - Adriana Cheavegatti-Gianotto; Hellen Marília Couto de Abreu; Paulo Arruda; João Carlos Bespalhok Filho; William Lee Burnquist; Silvana Creste; Luciana di Ciero; Jesus Aparecido Ferro; Antônio Vargas de Oliveira Figueira; Tarciso de Sousa Filgueiras; Mária de Fátima Grossi-de-Sá; Elio Cesar Guzzo; et al. (Tropical Plant Biology, 2011)

Monosialoanglioside (GM1) prevents lead-induced neurotoxicity on long-term potentiation, SOD activity, MDA levels, and intracellular calcium levels of hippocampus in rats - Jia-Qi She; Ming Wang; Da-Miao Zhu; Mingliang Tang; Ju-Tao Chen; Lang Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Distribution patterns of interstitial polychaetes in sandy beaches of southern Brazil - Maikon Di Domenico; Paulo Da Cunha Lana; André R. S. Garraffoni (Marine Ecology, 2009)
This study describes the distribution patterns of interstitial polychaetes along morphodynamic gradients on six exposed sandy beaches in Santa Catarina and Paraná (South Brazil). Three random transects were sampled at two points on each beach, one at the swash and another at the surf zone, in winter and summer conditions. Six sediment replicates were collected at each sampling point using a corer of 4.6 cm internal diameter that removed 10 cm into the sediment. Abundance and composition of interstitial polychaete were correlated to wave height, slope, grain size, CaCO 3 , chlorophyll a , omega indexes, temperature and relative tide range using a canonical correspondence analysis (CCA). A factorial ANOVA showed that taxa richness, mean density and Shannon’s diversity were significantly higher at the reflective beaches, but average values differ significantly between transects and these differences change according to the beach zones on both sampling dates. PERMANOVA showed that polychaete associations differ among transects according to the beach zones. The composition of interstitial polychaete associations was significantly correlated to beach morphodynamics and features (P

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)